2019
DOI: 10.1017/thg.2019.54
|View full text |Cite
|
Sign up to set email alerts
|

The Older Finnish Twin Cohort — 45 Years of Follow-up

Abstract: The older Finnish Twin Cohort (FTC) was established in 1974. The baseline survey was in 1975, with two follow-up health surveys in 1981 and 1990. The fourth wave of assessments was done in three parts, with a questionnaire study of twins born during 1945–1957 in 2011–2012, while older twins were interviewed and screened for dementia in two time periods, between 1999 and 2007 for twins born before 1938 and between 2013 and 2017 for twins born in 1938–1944. The content of these wave 4 assessments is described an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

7
3

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 111 publications
(130 reference statements)
1
101
0
Order By: Relevance
“…Data on participants from three FTC (Old twin cohort, Finntwin16, and Finntwin12) (15,16) were included in this study (N = 11,528 for both genetic and self-reported PA data; mean age, 44 yr (range, 18-93 yr); 46% male participants). From a subgroup of the Old twin cohort, 765 individuals had both genetic and objectively measured PA data (MOBILETWIN study; mean age, 73 yr (range, 71-75 yr); 46% male participants) (17).…”
Section: Methodsmentioning
confidence: 99%
“…Data on participants from three FTC (Old twin cohort, Finntwin16, and Finntwin12) (15,16) were included in this study (N = 11,528 for both genetic and self-reported PA data; mean age, 44 yr (range, 18-93 yr); 46% male participants). From a subgroup of the Old twin cohort, 765 individuals had both genetic and objectively measured PA data (MOBILETWIN study; mean age, 73 yr (range, 71-75 yr); 46% male participants) (17).…”
Section: Methodsmentioning
confidence: 99%
“…The Older Finnish Twin Cohort includes twins born in Finland before 1958 where both twins in a pair are alive in 1975 [18,19]. As these pairs of the same gender were selected from the Central Population Registry of Finland in 1974, the Cohort is population-based and its overall mortality and cancer incidence does not differ from that of the general population [18,20].…”
Section: Population Samplementioning
confidence: 99%
“…National Institute for Health and Welfare Biobank for those participants with biosamples, please see Kaprio et al (2019) for our review paper on the older Finnish Twin Cohort.…”
Section: Methodsmentioning
confidence: 99%